Menakar Penerapan New Public Management dalam Birokrasi Indonesia - Winengan, Winengan (Jurnal Ilmiah Administrasi Publik, 2018)
The presence of New Public Management as a new paradigm of publicadministration is projected to provide solutions to the complexity of public sector issues. The New Public Management offers an the idea to improve public sector performance by transforming the spirit of private sector that prioritizes the value of effectiveness and efficiency. In Indonesian bureaucracy, the opportunity in applying â€œThe New Public Managementâ€ in strategic. Because of support bureaucratic reform policies that have been continuously buzzed by the government since the birth of the Reform Orde. In reality, applying is still constrained by the mental apparatus of bureaucracy that lack of commitment to make changes, the work culture of the organization is not creative, and the model of leadership that is not transformative.